Self-compensating liquid repellent surfaces with stratified morphology - Hu,S; Cao,X; Reddyhoff,T; Puhan,D; Vladescu,S-C; Wang,Q; Shi,X; Peng,Z; deMello,AJ; Dini,D (ACS Applied Materials and Interfaces, 2019)
Artificial liquid repellent surfaces have recently attracted vast scientific attention; however, achieving mechanical robustness remains a formidable challenge before industrialization can be realized. To this end, inspired by plateaus in geological landscapes, a self-compensating strategy is developed to pave the way for the synthesis of durable repellent surfaces. This self-compensating surface comprises tall hydrophobic structural elements, which can repel liquid droplets. When these elements are damaged, they expose shorter structural elements that also suspend the droplets and thus preserve interfacial repellency. An example of this plateau-inspired stratified surface was created by 3D direct laser lithography micro-nano fabrication. Even after being subjected to serious frictional damage, it maintained static repellency to water with a contact angle above 147 and was simultaneously able to endure high pressures arising from droplet impacts. Extending the scope of nature-inspired functional surfaces from conventional biomimetics to geological landscapes, this works demonstrates that the plateau-inspired self-compensating strategy can provide an unprecedented level of robustness in terms of sustained liquid repellency.